Safety and Efficacy of Rivaroxaban in Patients With Cardiac Implantable Electronic Devices: Observations From the ROCKET AF Trial. Issue 6 (June 2017) - Leef, George C.; Hellkamp, Anne S.; Patel, Manesh R.; Becker, Richard C.; Berkowitz, Scott D.; Breithardt, Günter; Halperin, Jonathan L.; Hankey, Graeme J.; Hacke, Werner; Nessel, Christopher C.; Singer, Daniel E.; Fox, Keith A.A.; et al.
Abstract : Background: Although implantation of cardiac implantable electronic devices (CIEDs) in patients receiving warfarin is well studied, limited data are available on the use of oral factor Xa inhibitors in this setting. Methods and Results: Using data from Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation (ROCKET AF) (n=14 264), we compared baseline characteristics and clinical outcomes in patients with atrial fibrillation randomized to rivaroxaban versus warfarin who did and did not undergo CIED implantation or revision. In this post‐hoc, postrandomization, on‐treatment analysis, only the first intervention per patient was analyzed. During a median follow‐up of 2.2 years, 453 patients (242 rivaroxaban group; 211 warfarin group) underwent de novo CIED implantation (64.2%) or revision procedures (35.8%). Patients who received CIEDs were older, more likely to be male, and more likely to have past myocardial infarction, but had similar stroke risk compared to patients who did not receive CIEDs. Most patients who received a device had study drug interrupted for the procedure and did not receive bridging anticoagulation. During the 30‐day postprocedural period, 11 patients (4.55%) in the rivaroxaban group experienced bleeding complications compared with 15 (7.13%) in the warfarin group. Thromboembolic complications occurred in 3 patients (1.26%) in the rivaroxaban group and 1 (0.48%) in the warfarin group. Event rates were too low for formal hypothesis testing. Conclusions: Bleeding and thromboembolic events were low in both rivaroxaban‐ and warfarin‐treated patients. Periprocedural use of oral factor Xa inhibitors in CIED implantation requires further study in prospective, randomized trials. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00403767.